Tributyltin (TBT) Degrading Bacteria as a Tool for the Remediation of Organotin Pollution from Water Sediments - Iqbal, Muhammad Naeem; Ashraf, Asfa (PSM Biological Research, 2024)
Despite global restrictions on the usage of organotin (OT), a significant quantity of OT is being released into aquatic habitats due to the growth of industry and agriculture. Microorganisms from polluted sites can develop a tolerance to pollutants and, in some cases, degrade them, which can be a crucial factor in the recovery of contaminated environments. Microbes may convert the toxic compound Tributyltin (TBT) into less or non-toxic products, dibutyltin (DBT), monobutyltin (MBT), or use TBT as a carbon source. In this issue, Ebah et al. (2024) report that Bacillus spp., and Pseudomonas spp., isolates were more efficient among other isolates, with the main goal of determining the potential of these isolates to bioremediate TBT into less toxic compounds. In particular, isolates that demonstrated a higher TBT reduction of the sediment had the most potential for use in TBT bioremediation at polluted sites. Therefore, using nature-based solutions, such as bioremediation, is a viable way to remove TBT from water sediments.